Seperti Apa Pemahaman Konsep Geometri Bangun Datar Anak Tunarungu dalam Pembelajaran Menggunakan Video Audio-Visual Colour Guard (AVCG)? - Dea Devi Anggraeni; Indah Rahayu Panglipur; Lutfiyah Lutfiyah (Universitas Islam Jember, 2026)
This study aims to analyze students' understanding of flat geometry concepts through the application of Colour Guard audio-visual videos. The study uses a qualitative descriptive method with three deaf students in grade IX at the Jember State Special School as subjects. Data collection techniques included observation, interviews, documentation, and written tests. The Colour Guard audio-visual video was used as a learning medium to help students understand flat shape concepts visually. The results of the study indicate that the use of the Colour Guard audio-visual video was able to improve students' understanding of flat shape geometry concepts, as indicated by increased activity, attention, and written test results. In addition, students responded positively to the learning media because of its clear and attractive visual presentation, which facilitated their understanding of the concepts. This media can be said to be suitable for supporting the learning of flat shape geometry for deaf students. Keywords: Conceptual Understanding, Plane Geometry, Deaf